Anamnesis - Zwartjes, Frans (The Netherlands, 1969)
The film in three parts follows a man and a woman, Zwartjes’ regular actors Trix and Lodewijk de Boer, circle around each other, both in the house and outside beside the water, repelling and attracting each other.
Black and White
No dialogue
Verzio Film Festival Submission
Keywords: Experimental films